Efficient control representation in Digital Twins: an imperative challenge for declarative languages - Cimino, Chiara; Terraneo, Federico; Ferretti, Gianni; Leva, Alberto (IEEE transactions on industrial informatics, 2023)
Digital Twins (DTs) are enablers for the fast optimisation processes required in the Industry 4.0 context. Declarative equation-based modelling languages, in turn, enable the creation of large-scale simulation-based DTs, as they relieve the analyst from creating the solution code. However, most industrial assets are Cyber-Physical Systems (CPSs), the Cyber part being their digital controls. With the available technology, a precise representation of modulating and logic controls conflicts with DT simulation performance. The result is a barrier to using DTs for system-level optimisation. We analyse the problem, propose a modelling paradigm to solve it and suggest how to integrate that paradigm into equation-based language compilers. We support our proposal by presenting a Modelica/C++ library, that we release as free software, built according to the said paradigm.